Numerical investigation of novel dehumidification strategies in nuclear plant steam turbine based on the modified nucleation model. (November 2019) - Zhang, Guojie; Zhang, Xinzhe; Wang, Fangfang; Wang, Dingbiao; Jin, Zunlong; Zhou, Zhongning
Highlights: The modified nucleation model is built. Five novel dehumidification strategies are presented. The LWE has the best dehumidification effect, reducing the wetness loss to 2.67 kJ/kg. The dehumidification structure with 8 passage reduces the wetness loss to 2.51 kJ/kg. Abstract: To decrease the wetness loss and increase the safety in nuclear plant steam turbine, several novel dehumidification strategies are presented in this paper and the dehumidification effect is tested by employing the modified model. The modified nucleation model is built firstly, and the accuracy of the modified nucleation model combined with several droplet growth models is investigated and discussed, the results show that the modified nucleation model combined with the Young's droplet growth model ( ϕ = 0.75, α = 9 ) shows a satisfactory ability to describe the non-equilibrium condensation process. Secondly, the non-equilibrium condensation characteristic is studied in Dykas cascade, the relationship among the parameters is obtained, four phases and five feature nodes of the non-equilibrium condensation process are revealed, which provides a basis for the dehumidification strategy study. Thirdly, five novel dehumidification strategies are presented, and the dehumidification effect is evaluated. The results show that the passage adopted in the LWE (Location of the wetness emerging) has the best dehumidification effect, which lays the foundation for the dehumidification study in nuclear plant steam turbine three-dimensional cascade. Fourthly, the non-equilibrium condensation characteristic is studied numerically in nuclear plant steam turbine, with the span increasing, the LMF (Liquid mass fraction) gradually reduces. At last, the dehumidification strategies with different passage layers are investigated and whose effect are analyzed and discussed. With the passage number increasing, the LMF decreases quickly, and the location of the LMF forming moves backward gradually. Besides, when the passage layer increases to 8, the dehumidification effect almost keeps constant, and the wetness loss is reduced from 3.01 kJ/kg to 2.51 kJ/kg, the dehumidification effect is remarkable. The results in this paper can give a scientific basis and reference for the nuclear plant steam turbine design and dehumidification strategy optimization. Graphical abstract: Image, graphical abstract